Trends in the treatment for liver metastasis of colorectal cancer in Japan - Maruta, M; Maeda, K (Rozhledy v chirurgii, 2011)
The rate of liver metastasis before surgery of colorectal cancer is 11% in Japan. The survival rate of radical surgery with D-3 lymph node adenectomy is 83.7% in colon cancer and 77.1% in rectal cancer. The percentage of recurrent liver metastasis after curative surgery with D-3 lymph node extent resection is 7.1% within 5 years. Hepatectomy has the best survival rate: 52.8% after 3 years, 39.2% after 5 years. There is no difference in patients' survival rate between systemic anatomical hepatectomy and non-anatomical limited resection. For recurrent hepatic metastasis after curative surgery, hepatectomy should be done if no other metastasis is found in any other organ and the patient is suitable for surgery. Hepatic artery infusion chemotherapy (HAI) for metastasis of the liver is no longer used today. Radiofrequency ablation or microwave coagulation therapy may prolong the survival time but is not a curative procedure.
Keywords: nádory jater; Humans; Japonsko; Antineoplastic Agents; Hepatectomy; lidé; intraarteriální infuze; Liver Neoplasms; Lymph Node Excision; Japan; hepatektomie; kolorektální nádory; Infusions, Intra-Arterial; protinádorové látky; lymfadenektomie; lokální recidiva nádoru; míra přežití; Neoplasm Recurrence, Local; Colorectal Neoplasms; Survival Rate